Evidence of natural selection and dominance of SARS-CoV-2 variant Lambda (C.37) over variants of concern in Cusco, Peru - Maria Antonieta Quispe-Ricalde; Hugo G. Castelán-Sánchez; Pablo M. Meza-Rodríguez; Sonia Dávila-Ramos; José Luis Sierra; Ramón Batista-Garcia; Fátima Concha-Velasco; Sonia Flores Lucana; José De Santa Cruz; Víctor Zea; Marco Galarza; Omar Caceres-Rey; et al. (Archives of Virology, 2023)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) lineage C.37 (Lambda) has spread rapidly in Peru and other Latin American countries. However, most studies in Peru have focused on Lima, the capital city, without knowing the dynamics of the spread of the variant in other departments. Cusco, Peru, is one of the most popular departments in the country for tourists, so the introduction of new variants of SARS-CoV-2 might occur despite closure of the borders. Therefore, in this work, we analyzed the variants circulating in Cusco. The aim of this work was to better understand the distribution of SARS-CoV-2 lineages circulating in Cusco and to characterize the genomes of these strains. To this end, 46 SARS-CoV-2 genomes from vaccinated and unvaccinated patients were sequenced in the first half of 2021. The genomes were analyzed using phylogenetic and natural selection methods. Phylogenetic trees from Cusco showed dominance of the Lambda lineage over the variants of concern (VOCs), and there was no clustering of variants by district. Natural selection analysis revealed mutations, mainly in the spike protein, at positions 75, 246, 247, 707, 769, and 1020. In addition, we found that unvaccinated patients accumulated more new mutations than did vaccinated patients, and these included the F101Y mutation in ORF7a, E419A in NSP3, a deletion in S (21,618-22,501), and a deletion in ORF3a (25,437-26,122).